Designing learner-centred text-based feedback: a rapid review and qualitative synthesis. Issue 6 (17th August 2021) - Ryan, Tracii; Henderson, Michael; Ryan, Kris; Kennedy, Gregor
Abstract: Current conceptualisations of feedback contend that it should be a learner-centred process. In practice, however, text-based feedback comments from teachers are a convenient and common source of feedback information, despite appearing to be contra-indicative of learner-centred models. This raises the question of how teachers can tackle the design of text-based learner-centred feedback, but at present there is limited empirical evidence available to answer this question. In response, we conducted a rapid review and qualitative synthesis of 95 peer-reviewed scholarly publications on feedback, and appraised the results through the lens of four diverse conceptualisations of learner-centred feedback. This process led to the development of a framework of 12 learner-centred design attributes for text-based feedback, which were organised around three layers of design: contexts, characteristics and components. Each of these design attributes are discussed and practical recommendations are synthesised from the literature. Areas in need of additional empirical research are also highlighted.